PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA INOVASI EMITEN JAKARTA ISLAMIC INDEX TAHUN 2021-2023 - Riski Dwi Anggraini; Rachma Agustina (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2026)
This study aims to analyze the effects of Human Capital Efficiency (HCE), Capital Employed Efficiency (CEE), Structural Capital Efficiency (SCE), and Relational Capital Efficiency (RCE) on innovation performance among issuers included in the Jakarta Islamic Index (JII) during the 2021–2023 period. This study employs an approach using data obtained from the reports and financial statements of the companies. The sampling technique used is purposive sampling, based on criteria requiring companies to be listed in the JII throughout the observation period and to provide the data necessary to measure the research variables. Data were analyzed using multiple linear regression with the assistance of SPSS 25. Hypothesis testing consisted of the t-test to examine the partial effect of each independent variable, the F-test to assess the simultaneous effect of the independent variables, and the coefficient of determination to evaluate the model’s ability to explain variations in innovation performance. The results indicate that HCE, CEE, and RCE have no significant effect on innovation performance. In contrast, SCE has a significant effect on innovation performance.